2011
DOI: 10.1007/s10896-011-9399-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Revictimization of Intimate Partner Violence: The Role of Attachment, Anger and Violent Behavior of the Victim

Abstract: Victims of intimate partner violence (IPV) are known to be at high risk for revictimization. Yet, to date, the mechanisms explaining the link between victimization and revictimization of IPV have not been extensively studied. In the present prospective study involving 74 female help-seeking victims of IPV, we investigated victim-related psychological mechanisms that may underlie this link. With this study, we aim to contribute to the development of theory addressing these psychological mechanisms and their rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 44 publications
5
84
0
1
Order By: Relevance
“…Finally, this study only evaluated IPV victimization; therefore, it is unknown whether participants in this study also engaged in IPV, including bidirectional violence. Evaluating anger-related dysregulation as a mechanism linking childhood family violence exposure to bidirectional aggression is a promising avenue for future research (Kuijpers, van der Knaap, & Winkel, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study only evaluated IPV victimization; therefore, it is unknown whether participants in this study also engaged in IPV, including bidirectional violence. Evaluating anger-related dysregulation as a mechanism linking childhood family violence exposure to bidirectional aggression is a promising avenue for future research (Kuijpers, van der Knaap, & Winkel, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…These results, along with a longitudinal study by Feld and Straus (1989) indicate that a woman's perpetration of violence is a strong predictor of her being a victim of partner violence. This includes longitudinal studies, by Feld and Straus (1989), Kuijpers, van der Knaap, andWinkel (2011), andLorber andO'Leary (2011), and cross-sectional studies by O'Keefe (1997), Whitaker, Haileyesus, Swahn, and Saltzman (2007). Still other studies are reviewed in the meta-analysis by Stith, Smith, Penn, Ward, and Tritt (2004), which concluded that violence by the female partner is the largest single risk factor for victimization of women.…”
Section: Services For Victims and Offendersmentioning
confidence: 99%
“…Approximately one-third (34%) of perpetrator motivations noted in open-source material of United States campus attacks included intimate partner conflicts (Drysdale et al, 2010), and extensive review of repetitive and escalating intimate partner violence exists (Jenkins, 2009;Kuijpers, van der Knaap, & Winkel, 2012;Tjaden & Thoennes, 2000;Yamawaki et al, 2012). In a United States national survey, approximately 70% of men and women suffering from intimate partner victimization reported maintaining their partnership with the offender (Tjaden & Thoennes, 2000).…”
Section: Addressing Remaining Questions About Pre-incident Behaviormentioning
confidence: 99%
“…These victims have described offenders utilizing a range of violent behaviors (e.g., threats, weapon use, harassing behavior, physical violence, and rape), and half of affected women (45%) and one-quarter of affected men (25%) indicated fearing the perpetrator would cause severe harm and/or death. Surveys of United States perpetrators have displayed intimate partner violence escalating in severity (i.e., with one year between surveys; Okuda et al, 2015), especially with victim attempts to leave the relationship or physically fight back (Jenkins, 2009;Kuijpers et al, 2012). Perpetrators' prior physical aggressiveness, threats to kill, and weapon accessibility correspond with lethal force (i.e., in comparisons between abused women and homicide victims; Jenkins, 2009), and intimate partner homicides tend to follow estrangement.…”
Section: Addressing Remaining Questions About Pre-incident Behaviormentioning
confidence: 99%